Comparing the efficacy of yoga exercise and intergenerational interaction program on mental health of elderly - Zeanat Ebrahimi; Mohamad Reza Esmaeilzadeh Ghandehary; Kourosh Veisi (Gonabad University of Medical Sciences, 2019)
Wellness is defined as physical, psychological and social well-being, not just the lack of disease and physical handicap. This study aimed at comparing the effects of two intergenerational programs and yoga exercises on the mental health of the elderly. The research was based on a quasi-experimental approach with control group and posttest design. The statistical population consisted of Young and old people living. 175 elders were selected using a randomized cluster sampling method and then randomly assigned to two experimental groups and one control group. Demographic questionnaires, socio-economic status and general health (GHQ-28) were used as research tools. Data were analyzed in two stages before and three months after intervention. The elderly included 95 males, 80 females aged 71.89 ± 8.38 years and 60 youth aged 21.45 ± 0.35 years on mean. The results showed that the intergenerational program and yoga exercises significantly improved scores for mental health and all its subscales. The intergenerational program with a substantial reduction in scores in two sub-scales of social dysfunction and depression had the same effect as yoga exercises. But it had less impact on somatic symptoms and anxiety-sleep disorders. Considering the research findings in confirming the effectiveness of intergenerational programs and yoga exercises on elderly people's mental health, it is suggested that these programs be considered by planners in health and welfare organizations and institutions.